Flooding stress influences productivity and modulates biodiversity effects in experimental grassland communities, shaping biodiversity–productivity relationships - Zhekov, Aleksandar; Bourgeois, Bérenger; Poulin, Monique (American Journal of Botany, 2025)
Abstract Premise Biodiversity loss and increasing extreme weather events disrupt the functioning of ecosystems and thus their ability to provide services. While the interplay among various climatic constraints, diversity and productivity has received increasing attention in the last decades, the role of flooding has been overlooked. Methods In a greenhouse experiment, we manipulated species richness and water regimes to evaluate the influence of flooding on species diversity–productivity relationships. We measured biomass production and partitioned net biodiversity effects into complementarity and selection effects. To link changes in biodiversity effects to underlying mechanisms, we evaluated the contribution of species richness, species identity, functional diversity and community‐level traits. Results Under flooding, biomass production decreased, and biodiversity effects were less frequently positive. By reducing the incidence of positive complementarity effects, flooding promoted a preponderance of selection effects. Flooding further favored competitive displacement by Phalaris arundinacea ; balanced contributions to selection effects from all functional groups at field capacity subsided under flooding when P. arundinacea became the single dominant species. As a result, its acquisitive leaf trait attributes contributed more to selection effects and biomass production under flooding, while root traits contributed less to complementarity effects at field capacity. Conclusions As an environmental stressor, flooding promoted the dominance of tolerant species and reduced the incidence of complementary species interactions in the experimental plant communities, clearly modulating the linkage between diversity and productivity.
Keywords: Infolettre_Septembre_2025

Establishing perennial strips in a cultivated floodplain for habitat restoration: monitoring over 4 years and success drivers - Damar, Hada; Vaillancourt, Mathieu; Bourgeois, Bérenger; Poulin, Monique (Restoration Ecology, 2024)
Floodplains, one of the most biologically diverse and productive ecosystems, are under threat from intensive crop production. Implementing perennial strips alongside agricultural ditches and streams could reduce negative impacts of intensive agriculture and restore wildlife habitats in cultivated floodplains. To successfully set up perennial strips, it is important to understand the parameters that drive their establishment. Here we assessed the establishment success of reed canarygrass (RCG; Phalaris arundinacea ) strips in the lake Saint Pierre (LSP) floodplain, Québec, Canada by monitoring RCG biomass and vegetation height over 4 years and identify the factors driving its establishment. A total of 26 RCG strips across six municipalities of LSP were monitored. Biomass and vegetation height of RCG increased over time to reach an average of 5048 kg/ha in year 4 and 104 cm in year 3 in established strips. The RCG established successfully in 62% of surveyed plots and three environmental parameters explained 61% of this success. Establishment of RCG was most successful when a first rain came right after seeding (<3 days). High clay content and low elevation were associated with establishment failures. Overall, our results highlight the ability of RCG strips to restore dense perennial vegetation cover in cultivated floodplain, thereby providing suitable habitat for fish spawning during spring floods. This study provides significant insight into the drivers of establishment of perennial grass strips in highly constrained cultivated areas such as floodplains.
Keywords: Infolettre; Infolettre_Novembre_2024

Establishment of reed canarygrass ( Phalaris arundinacea ) in the context of floodplain restoration: impact of companion plant and sowing rate - Vaillancourt, Mathieu; Čapkun-Huot, Catherine; Jean Jacques, Samuel; Bourgeois, Bérenger; Poulin, Monique (Botany, 2024)
Habitat loss and degradation is a leading cause of the current biodiversity crisis. In the lake Saint-Pierre floodplain, agricultural intensification has led to the loss of substantial spawning and rearing areas for the yellow perch ( Perca flavescens Mitchill). Restoring perennial vegetation cover is key to ensure the persistence of the population, but the floodplain conditions limit our ability to do so. In this study, we tested the impact of companion plants ( Avena sativa L., Lolium multiflorum L.) and sowing rate on the establishment success of reed canarygrass ( Phalaris arundinacea L.; RCG) in year 2. RCG tolerates a wide range of environmental conditions and can provide the plant cover essential to the reproduction of yellow perch. We hypothesized that companion plants would reduce weed pressure and in turn improve RCG establishment, and that increasing the sowing rate would improve the establishment success. Contrary to our expectations, using companion plants generally reduced the cover and biomass of RCG. It also led to increased weed prevalence in most treatments. In addition, sowing at high rates did not impact RCG cover and biomass. Sowing RCG alone appears to be the most effective option to establish perennial vegetation supporting the recovery of the yellow perch population.
Keywords: Infolettre; Infolettre_Mai_2024

Towards sustainable agricultural landscapes: Lessons from an interdisciplinary research-based framework applied to the Saint Lawrence floodplain - Watson, Christopher J; Mazzei, Renata; Bourgeois, Bérenger; Smedbol, Élise; Guiraud, Noé; Félix-Faure, Jim; Damar, Hada; Tremblay, Maxime; Bordeleau, Pierre-Andé; Vaillancourt, Mathieu; Bertolo, Andrea; Cabana, Gilbert; et al. (Basic and Applied Ecology, 2024)
Keywords: Infolettre; Infolettre_Octobre_2024